Yttrium-90 TOF-PET-Based EUD Predicts Response Post Liver Radioembolizations Using Recommended Manufacturer FDG Reconstruction Parameters - Hesse, Michel; d’Abadie, Philipe; Lhommel, Renaud; Jamar, Francois; Walrand, Stephan (Frontiers in Oncology, 2021)
Purpose: Explaining why 90Y TOF-PET based equivalent uniform dose (EUD) using recommended manufacturer FDG reconstruction parameters has been shown to predict response. Methods: The hot rods insert of a Jaszczak deluxe phantom was partially filled with a 2.65 GBq 90Y - 300ml DTPA water solution resulting in a 100 Gy mean absorbed dose in the 6 sectors. A two bed 20min/position acquisition was performed on a 550ps- and on a 320ps- TOF-PET/CT and reconstructed with recommended manufacturer FDG reconstruction parameters, without and with additional filtering. The whole procedure was repeated on both PET after adding 300ml of water (50Gy setup). The phantom was acquired again after decay by a factor 10 (5Gy setup), but with 200min per bed position. For comparison the phantom was also acquired with 18F activity corresponding to a clinical FDG whole body acquisition. Results: The 100Gy-setup provided a hot rod sectors image almost as good as for the 18F phantom. However, despite acquisition time compensation the 5Gy-setup provides much lower quality imaging. TOF-PET based sectors EUDs for the three large rod sectors were in agreement with the actual EUDs computed with a radiosensitivity of 0.021Gy-1 well in the range observed in external beam radiotherapy (EBRT), i.e. 0.01-0.04Gy-1. This agreement explains the reunification of the dose-response relationships of the glass and resin spheres in HCC using the TOF-PET based EUD. Additional filtering reduced the EUDs agreement quality. Conclusions: Recommended manufacturer FDG reconstruction parameters are suitable in TOF-PET post 90Y liver radioembolization for accurate tumor EUD computation. The present results clearly rule out the use of low specific activity phantom studies to optimize reconstruction parameters.